A Practice of Choosing Gamification-based Personas - Liu, Shunli; Idris, Muhammad Zaffwan (Archives of Business Research, 2020)
This study contributes our entire research project on museum user experience (UX), and the purpose of the paper is to provide knowledge in practice for choosing Gamification-motivated personas. As the player’s motivation fundamentally drives the outcomes, the Bartle Test of Gamer Psychology reigning from types of players was employed as a persona tool for identifying personas representing distinct intrinsic motivations. Specifically, adhering to the philosophy of user-centric intrinsic motivation, Bartle drew on an extensive range of sources to identify four types of players: achievers, socializers, explorers, and killers (we re-name killers as attackers). By analyzing the gamer psychology, it can be connected the player types to the intrinsic needs in the Self-Determination Theory (SDT). From a methodological point of view, the combination approach of quantitative and qualitative methods with constantly narrowing the scope of candidate can benefit trustworthiness. As a practical study, this paper not only analyzes the principles, but also provides a detailed persona selection procedure.